2022
DOI: 10.3389/fimmu.2022.967944
|View full text |Cite
|
Sign up to set email alerts
|

Intrahepatic activated leukocyte cell adhesion molecule induces CD6highCD4+ T cell infiltration in autoimmune hepatitis

Abstract: Background and objectivesAutoimmune hepatitis (AIH) is characterized by the expansion and accumulation of pathogenic T cells in liver. Although CD6 and its ligand activated leukocyte cell adhesion molecule (ALCAM) are involved in the evolution of multiple inflammatory diseases, their roles in the pathogenesis of AIH remain unknown. Herein, we aimed to investigate ALCAM-CD6 axis in AIH development.MethodsImmunohistochemistry was performed to examine hepatic expression of CD6 and ALCAM. The concentration of seru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…This study successfully identified specific urine proteins, namely activated leukocyte cell adhesion molecule (ALCAM), hemopexin (HPX), and peroxiredoxin 6 (PRDX6), which were found to be effective in identifying the disease ( 8 , 9 ). ALCAM, also known as cluster of differentiation 166 (CD166), is a cell surface protein involved in inflammation and immune responses ( 10 ). HPX is a protein that regulates heme biology to maintain iron balance.…”
Section: Introductionmentioning
confidence: 99%
“…This study successfully identified specific urine proteins, namely activated leukocyte cell adhesion molecule (ALCAM), hemopexin (HPX), and peroxiredoxin 6 (PRDX6), which were found to be effective in identifying the disease ( 8 , 9 ). ALCAM, also known as cluster of differentiation 166 (CD166), is a cell surface protein involved in inflammation and immune responses ( 10 ). HPX is a protein that regulates heme biology to maintain iron balance.…”
Section: Introductionmentioning
confidence: 99%